Interscapular brown adipose tissue recruitment is hindered by a temperature environment of 33°C: uncoupling protein-1 underexpression is not associated with obesity development in rats - Jurić-Lekić, Gordana; Bedrica, Ljiljana; Lončar, Dragutin (Archives of Biological Sciences, 2018)
Paper description: In rat’s brown adipose tissue (BAT), cold environment recruits adipocytes, stimulates Uncoupling protein-1 (UCP-1) expression and development of specific, uncoupled mitochondria (UC-mitochondria). The authors showed that at thermoneutral environment of 33°C, rat pups failed to recruit BAT. The tissue remains atrophic, composed of preadipocytes and adipocytes that are smaller but packed with lipids and UC-mitochondria, having 9-fold less of UCP-1 and newly described intramitochondrial inclusions. In BAT of pups raised at 33°C, underexpression of UCP-1 does not lead to obesity; lack of UCP-1 does not affect proliferation of UC-mitochondria but may contribute to development of intramitochondrial inclusions. Abstract: Brown adipose tissue (BAT) generates heat due to unique thermogenic UC-mitochondria, an event known as nonshivering thermogenesis. Cold, adrenergic agents, hormones, etc., activate nonshivering thermogenesis, resulting in lipid mobilization, an increase in the mitochondria and mitochondrial cristae, and increased uncoupling protein-1 (UCP1) expression and its incorporation into mitochondrial cristae. BAT precursor cells mature and contribute to BAT growth in a process known as BAT recruitment. For the first time, we herein report the effect of a thermoneutral environment of 33°C on interscapular BAT (IBAT) in rats delivered and raised at 33°C. The control animals were housed at 20°C. Thermoneutral IBAT was atrophic (73 mg vs. 191 mg) but with more adipocyte precursor cells; euthermia (37.6°C) was maintained without nonshivering thermogenesis. Although IBAT was inactive, the thermoneutral animals did not develop obesity, and on the contrary, the thermoneutral environment of 33°C hindered the rats’ growth, weight (65 gm vs. 139 gm), volume (67 gm vs.136 gm) and length (12 cm vs. 16 cm). The thermoneutral brown adipocytes were smaller (7234 µm3 vs. 9198 µm3) with more lipids (4919 µm3 vs. 4507 µm3) and a smaller mitochondrial cristae area (52504 µm2 vs. 61288 µm2/adipocyte). Lipoprotein lipase mRNA expression was 11% (vs. 58% in control) and UCP1 mRNA expression was 34% (vs. 93% control). UCP1 immunoelectron microscopic study detected 160 UCP1-gold particles (vs. 700 in control) per UC-mitochondrion; thermoneutral brown adipocytes had 9-fold fewer UCP1-gold particles (0.34x106 vs. 2.99x106 UCP1-gold particles), and thermoneutral UC-mitochondria developed specific intramitochondrial tubular inclusions. https://doi.org/10.2298/ABS171215018J Received: December 15, 2017; Revised: March 7, 2018; Accepted: April 18, 2018; Published online: May14, 2018 How to cite this article: Jurić-Lekić G, Bedrica Lj, Lončar D. Interscapular brown adipose tissue recruitment is hindered by a temperature environment of 33°C: Uncoupling protein-1 underexpression is not associated with obesity development in rats. Arch Biol Sci. 2018;70(3):…